The Successful Scientific Publication: The Bulgarian Practice Against the International Standards [In Bulgarian] - B.V. Toshev (University of Sofia, 2008)
The paper describes the world system of indexing, abstracting and evaluation of the primary scholarly journals. The international standards of academic publishing are listed and commented. The particularities of the Bulgarian publication practice are discussed. The harmonization of both systems, Bulgarian and international, will facilitate the process of inclusion of Bulgaria in the common European research and education area.